Primary computing & digital technologies knowledge, understanding & practice - Turvey, Keith; Burton, Jeremy; Allen, Jonathan (Lecturer in information technology); Potter, John (Reader in Media in Education); Sharp, Jane 1966- (Achieving QTS Series., 2016)
What do you need to know to teach?computing in primary schools? How do you teach it? This book provides practical guidance on how to teach?the computing curriculum in primary schools alongside the necessary subject knowledge. It explores teaching and learning with ICT and digital technologies, addressing the role of the professional teacher with regards to important issues such as e-safety.